A HEAVY DIAGNOSIS: CUSHING’S SYNDROME SECONDARY TO ADRENAL CORTICAL ADENOMA - Yap, Suh Huey; Yeap, Cai Fong; Lordudass, Alexis (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Cushing’s syndrome (CS) is very rare in childhood and adolescence. It may present as a diagnostic dilemma among clinicians. CASE We report an 11-year-old male with hypertensive emergency, congestive heart failure, pulmonary oedema and acute kidney injury. He had a two-year history of rapid weight gain and symptoms of obstructive sleep apnoea. He was obese with a body-mass-index (BMI) of 47 kg/m² (weight 109 kg, >95th centile; height 152 cm, 90th centile). He appeared depressed with severe acanthosis nigricans, truncal obesity, dorsocervical fat pad, striae and virilized. He required intravenous labetalol and four antihypertensives on admission. Echocardiography revealed left ventricular impaired function (ejection fraction of 45%). Abdominal ultrasonography showed a left suprarenal lesion without renal artery stenosis. Abdominal computed tomography confirmed a lesion at the left suprarenal region (4.9 x 6.3 x 4.7 cm) and a right simple renal cyst. Urine biogenic amines and metanephrines were normal. He had elevated urinary cortisol at 3,574 nmol/24 hour (160–1,112) with loss of diurnal variation on salivary cortisol [midnight: 13.4 nmol/L (<11.3) and morning: 0.9 nmol/L (<24.1)] and on serum cortisol (midnight: 341.4 nmol/L and morning: 360.8 nmol/L). Further tests revealed suppressed ACTH: <0.33 pmol/L, and elevated serum dehydroepiandrosterone sulphate (DHEAS): 7.210 µmol/L (0.660–6.700). There was no suppression on low- and high-dose dexamethasone suppression tests, consistent with ACTH-independent CS. He underwent laparoscopic adrenalectomy, revealing an 8 x 5 cm, well-encapsulated left adrenal tumour. Preliminary histopathological analysis suggests adrenal adenoma. Perioperatively, he required stress-dose hydrocortisone (100 mg/m²/day) and tapered to a physiological dose (7 mg/m²/day) upon discharge. At follow-up, he was on two antihypertensive medications, demonstrated improved cardiac function (EF: 55%) and weight reduction (97 kg). CONCLUSION Although CS is rare in children, high levels of suspicion should be applied to those presenting with rapid onset obesity, hypertension and/or virilisation. Diagnosis of CS involves multiple investigative steps to guide treatment.